2022
DOI: 10.2147/ijn.s353071
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Coating: Tracheal Tube Application

Abstract: Ventilator-associated pneumonia (VAP) is a common and serious nosocomial infection in mechanically ventilated patients, increasing mortality, prolonging the patient length of stay, and increasing costs. In recent years, extensive studies on ventilator-associated pneumonia have shown that tracheal intubation plays an essential role in the pathogenesis of VAP, with the primary mechanism being the rapid colonization of the tracheal intubation surface by microbiota. Antibiotics do not combat microbial airway colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…In patients with sepsis, this risk of developing ICU-acquired infection is influenced by multiple interrelated factors. For example, some studies from 10 years ago with small sample sizes or covering a short period of ( Chen et al., 2022 ) time showed that advanced age, disease severity, deep venous catheterization, and invasive ventilation were associated with an increased risk of incident ICU-acquired infection in sepsis ( Wolkewitz et al., 2014 ; van Vught et al., 2016 ; Chen et al., 2019 ). Despite associations of lower human leukocyte antigen expression and increased interleukin-10 (IL-10) levels with ICU-acquired infection ( van Vught et al., 2017 ; Stortz et al., 2018 ), identifying which patients are at a higher risk of sepsis-associated ICU-acquired infection remains clinically challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with sepsis, this risk of developing ICU-acquired infection is influenced by multiple interrelated factors. For example, some studies from 10 years ago with small sample sizes or covering a short period of ( Chen et al., 2022 ) time showed that advanced age, disease severity, deep venous catheterization, and invasive ventilation were associated with an increased risk of incident ICU-acquired infection in sepsis ( Wolkewitz et al., 2014 ; van Vught et al., 2016 ; Chen et al., 2019 ). Despite associations of lower human leukocyte antigen expression and increased interleukin-10 (IL-10) levels with ICU-acquired infection ( van Vught et al., 2017 ; Stortz et al., 2018 ), identifying which patients are at a higher risk of sepsis-associated ICU-acquired infection remains clinically challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The minimal intracuff pressure could however lead to an increased incidence of regurgitation/aspiration and VAP development. Polyurethane seems to be a material superior to PVC for the cuff; however, tube or cuff coating with silver [ 94 ], antibiotics [ 95 ] or even nanomaterials to decrease the biofilm formation and VAP incidence could be the source for further tracheal tube research in the future.…”
Section: Ebm View and Future Perspectivesmentioning
confidence: 99%
“…One approach to hinder the adhesion and colonization of planktonic bacteria onto implants involves incorporating an antimicrobial surface onto the device. Over the past few decades, various antimicrobial agents such as antibiotics, , peptides, , polymers, and nanoparticles , have been utilized for modifying implants and creating bactericidal coatings. These functionalized implants can effectively impede the initial adhesion of planktonic bacteria while also inactivating surface-adherent bacteria to disrupt biofilm development.…”
Section: Introductionmentioning
confidence: 99%